2011
DOI: 10.5004/dwt.2011.2705
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of saline aqueous solutions using direct contact membrane distillation

Abstract: ab s t r ac tThe treatment of highly saline aqueous solutions using direct contact membrane distillation (DCMD) was evaluated in this study. Experiments were conducted using a flat sheet polytetrafluoroethylene membrane with nominal pore size of 0.22 µm. Seawater, reverse osmosis (RO) concentrate collected from a wastewater reclamation plant, and a synthetic solution containing 2,000 mg/L of CaSO 4 were selected as the representative saline solutions. A gradual decline in permeate flux was observed at the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…Such feeds might not provide an accurate indication of the capability of the commercial membranes to desalinate seawater. However there are few reported works using real seawater as feed for MD [38][39][40][41], but the obtained flux performances were very low compared to synthetic seawater.…”
Section: Compared To Other Conventional Desalination Processes Such Amentioning
confidence: 99%
“…Such feeds might not provide an accurate indication of the capability of the commercial membranes to desalinate seawater. However there are few reported works using real seawater as feed for MD [38][39][40][41], but the obtained flux performances were very low compared to synthetic seawater.…”
Section: Compared To Other Conventional Desalination Processes Such Amentioning
confidence: 99%
“…It is noteworthy that in the single-pass operation, the water recovery rate of the pilot AGMD system was noticeably low (i.e., 5%). Low water recovery rate together with a small concentration polarisation ensured that concentrations of potential scalants, such as CaCO3 and CaSO4 [24,32,33], at the membrane surface were well below their solubility limits. The stable distillate production rate (which indicates the absence of any membrane fouling) observed in this experiment can be also attributed to the low total organic carbon concentration of the seawater feed (i.e., 2 mg/L) and low operating permeate flux (i.e., 1.0 L/m 2 -h).…”
Section: Pilot Agmd Process Of Seawatermentioning
confidence: 99%
“…Recent studies reported the feasibility of treating many feed water types using MD such as salty water, impaired water resources, and CSG RO brine [3,9]. Duong et al [3] has successfully demonstrated a pilot-scale study of a spiral-wound air gap MD to treat CSG RO brine with 80% water recovery.…”
Section: Introductionmentioning
confidence: 99%